3D printed NMR spectra: From 1D and 2D acquisition to 3D visualization. (2nd April 2019) - Bakker, Michael; Boyd, Ben; Meints, Gary A.
Abstract: Visualization of two‐dimensional and relaxation NMR spectra can be difficult for students new to the subject. Educators have utilized 3D printing previously to demonstrate concepts such as potential energy surfaces and molecular orbitals, but this technology has yet to be used to create a visual model of NMR data. In order to address this, we have developed an approach for creating 3D printed models of two‐dimensional and inversion recovery spectra, which can then be used as an innovative teaching tool. This was done by converting raw FT NMR data into a 3D data graph using Mathematica . This graph is then converted into stereolithography format and printed using a 3D printer. These physical models will allow students to better understand the complex information presented in these NMR spectra.